Legal Protection for Buyers Against Cancellation of The Certificate of Land Rights Due to Administrative Defects - Ramadani, Moch Januar; Pujiwati, Yani; Rukmana, Yenni Yunithawati (Alauddin Law Development Journal, 2024)
The purpose of this research is to analyze the position of land rights certificates which were canceled by BPN due to administrative defects related to the status of land rights and legal protection for buyer. This research makes use of a normative juridical approach as its methodology. In this research, it is stated that Land Rights established on Management Rights and then transferred to third parties/buyers without permission from the Management Rights holder can be categorized as genuine but fake certificates (asphalt), so that such certificates are declared administratively defective and must be cancelled. Regarding protection for buyers whose certificates are later cancelled, legal protection can be implemented repressively, namely by the buyer getting compensation for the canceled certificate which should be the buyer’s right.